IMPLEMENTASI PROGRAM PEMBIASAAN BACA AL-QURAN SEBELUM PELAKSANAAN PEMBELAJARAN DI MADRASAH ALIYAH SUMATERA THAWALIB PARABEK - Agung Darmawan Siregar; Bambang Trisno; Jendrizal (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2024)
In this modern era, technological progress is increasingly rapid and human activities are always increasing, so that nowadays many people forget about religious activities, such as reciting the Koran, giving alms, and even not praying. Then with influence like this, it even reaches children, who follow the times. This research is entitled "Implementation of the Tadarus Al-Qur'an Familiarization Program Before Implementing Learning at Madrasah Aliyah Sumatra Thawalib Parabek". The aim of this research is to determine the implementation of strategies for habitual reading of the Al-Quran and determine the factors that influence the implementation of strategies for habitual reading of Al-Quran before teaching and learning activities (KBM) at MAS Sumatra Sumatra Thawalib. MAS Sumatra Thawalib Parabek is one of the madrasas that practices the habit of reading the Al- Quran before teaching and learning activities, which are carried out for 15 minutes, led by Santri who are in charge of reading the Al-Quran at that time. The type of research is qualitative research with a descriptive approach. This research pays attention to ongoing processes and events. The data analysis technique used is interactive analysis using three stages, namely data condensation, data presentation and conclusion drawing. The data source, namely primary data, is data obtained directly from the first data source, namely the madrasa head, tahfidz teacher and class X students. Secondary data sources, which come from old documents or administration of MAS Sumatra Thawalib Parabek. The results of the research are the steps implemented with slight modifications. Starting from reading the Al-Quran together or taking turns depending on the teacher's instructions, while listening, the educator provides motivation, ending with students reading the Koran prayer together. The supporting factors are the availability of the Koran in every class, a conducive environment, educators who have recitation skills and a recital of the Koran in class XII. Meanwhile, the inhibiting factor is the lack of time allocation and background which causes students' ability to read the Al-Quran to vary.